The criminal justice system on trial: Shaming, outrage, and gendered tensions in public responses to the Jian Ghomeshi verdict. (August 2018) - Coulling, Ryan; Johnston, Matthew S
Drawing on an affective framework, this qualitative content analysis of the immediate public responses on Twitter in the hours following Jian Ghomeshi's not guilty verdict (n = 3943 tweets) reveals two key discourses of public opinion. Twitter users depicted the criminal justice system (CJS) as having worked and/or failed, and these intensifying divisions were highly gendered. Members of the public pitted notions of the "rational male" against the "emotional female", and these debates heavily supported or opposed a patriarchal legal rationality. This study sheds light on the ways in which adversarial justice systems reproduce adversarial discourses on crime, and overlook the problems entangled in misleading applications of rationality to sexual consent. The wide circulation of blame to all parties involved in this case leads us to the conclusion that the CJS, in its current punitive form, does not instil a sense of confidence in the public. With a shifted focus on the healing and dignity of everyone involved in sexual assault cases, we recommend Restorative and Transformative approaches to justice as alternative measures to respond to sexual assault.